El síndrome de burnout y el rendimiento laboral de los empleados del área administrativa de la empresa DICOFHI, en la actualidad. - Mejía Banchón, Lisseth Abigail (2024)
Burnout syndrome is a condition of emotional exhaustion, depersonalization, and low personal accomplishment that significantly affects job performance. This study was conducted at DICOFHI, located in Lago Agrio, Ecuador, with the aim of analyzing the causes and effects of burnout syndrome among administrative staff. Using a mixed-methods approach combining qualitative and quantitative techniques, surveys, interviews, and focus groups were conducted with 40 administrative employees to identify the main causes and effects of burnout. The results showed that about 55% of employees often feel emotionally exhausted and about 80% report an emotional disconnect with their co-workers. In addition, 72.5% of employees rated their job stress level at 7 or higher on a scale of 1 to 10, and 55% feel dissatisfied with their job. The study revealed that lack of support and recognition by supervisors, coupled with an excessive workload and insufficient resources, are the main causes of burnout. The most significant effects include decreased productivity, increased errors, and mental and physical health problems. It is recommended to implement wellness programs, improve the work environment, and offer greater recognition to employees to mitigate these effects. In conclusion, burnout syndrome has a considerable impact on the job performance of DICOFHI's administrative staff. Implementing specific intervention strategies is crucial to improving employee well-being and, consequently, the company's efficiency and productivity.